PENERAPAN METODE STRUKTURAL ANALITIK SINTETIK (SAS) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR DAN KETERAMPILAN MEMAHAMI GAMBAR - Siti Aida; Bayu Insanistyo (UNIB Press, 2023)
The purpose of this study are to describe the application of SAS method to improve the thingking skills and image comprehension skills of children in Group B TK Negeri Pembina Merigi. The method used is classroom action research (PTK) which is carried out in 3 cycles and followed by a quasi-experimental. The research subjects for classroom in group B3 for control class B4 with 15 children and eksperimental class B2 with 15 children. Data was collected by using oral an action test techniques, while data analysis used t-tes with one simple test and independent simple test. The results showed a significant increase in cycles 1, 2 and 3. The application of the SAS method is appropriate to use improve children’s ability to think and understand pictutres an become the right alternative for learning